Burden of Herpes Zoster in Individuals with Immunocompromised Conditions and Autoimmune Diseases in the Republic of Korea: A Nationwide Population-Based Database Study - Jing Chen; Ju-Young Shin; Sumitra Shantakumar; Sungho Bea; Byong Duk Ye; Dong-Gun Lee; Hyungwoo Kim; Won Suk Choi; Iain Kaan (Infectious Diseases and Therapy, 2023)
Abstract Introduction To estimate herpes zoster (HZ) incidence rate (IR) and economic burden in individuals with immunocompromised conditions and autoimmune diseases (IC/AID) in the Republic of Korea (ROK). Methods The nationwide Health Insurance Review and Assessment Service database was used to identify HZ cases from 2016 to 2020 in ROK. HZ and non-HZ IC/AID cases were matched 1:3 using age, sex, institution, Charlson comorbidity index, IC/AID, and index date. Annual HZ IRs/1000 persons and 1-year HZ-associated all-cause direct medical costs for IC/AID cases were calculated. Results Among 65,976 individuals with IC/AID (mean age 57.14 years [standard deviation 14.1]; 64.94% female), annual HZ IR (95% confidence interval) fluctuated from 2016 to 2020, averaging 23.41/1000 persons (22.21–24.62) and was higher in women (26.85 [25.40–28.31]) than men (18.96 [18.03–19.89]). IRs were highest in individuals aged ≥ 50 years, and in those with transplants (including solid organ and hematopoietic stem cell transplants; 37.12 [35.45–38.79]) and hemato-oncology conditions (35.5 [31.6–39.3]). Mean 12-month all-cause direct medical costs were higher in individuals with IC/AID and HZ (4,759,671 Korean Republic won [KRW]; approximately 4046 United States dollar [USD; according to the 2020 conversion rate from UNCTAD; 1 KRW = 0.00085 USD]) than those without HZ (3,786,658 KRW; 3219 USD). Conclusion Individuals with IC/AID have a substantial disease and economic burden from HZ in ROK, highlighting the need for appropriate HZ prevention measures in the IC/AID population. Plain Language Summary